Respuesta :

For this case, we must find the value of the following expression:

[tex](\frac {2} {3}) ^ {- 4}[/tex]

By properties of powers we have that:

[tex]a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]

Thus, we can rewrite the expression as:

[tex]\frac {1} {(\frac {2} {3}) ^ 4} =\\\frac {3 ^ 4} {2 ^ 4} =\\\frac {81} {16}[/tex]

So, we have to:

[tex](\frac {2} {3}) ^ {- 4} = \frac {81} {16}[/tex]

Answer:

[tex]\frac {81} {16}[/tex]

Option D

Answer: Its D

Step-by-step explanation:

ACCESS MORE